PERAN KEMENTERIAN RISET, TEKNOLOGI DAN PENDIDIKAN TINGGI DALAM PENGUATAN SISTEM INOVASI DI INDONESIA(ROLE OF MINISTRY OF RESEARCH, TECHNOLOGY AND HIGHER EDUCATION FOR STRENGTHENING THE INNOVATION SYSTEM IN INDONESIA) - Budi Triyono (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2017)
Technological innovation is the key to the competitiveness of developed countries that have the innovation capability to become a strong country, respected and provide prosperity for its society. The technological innovation system plays an important role in generating innovation, especially in its industrial sector. Unfortunately, the resulting innovations of companies in various industrial sectors in Indonesia are generally only a simple innovation (incremental innovation) which is easily imitated by competitors and less supportive for its industrial competitiveness. Meanwhile, the increasing globalization and rapid technological revolution raise a serious challenge for companies to maintain their competitiveness. In this globalized economy, competition becomes more dynamic, which brings out the needs for radical innovation. Related to this, the Ministry of Research, Technology and Higher Education (Kemenristekdikti) whose task is to performing national research, technology and higher education should play a key role in the management of technology innovation system in Indonesia, include the organization of coordination and synchronization of innovation policy with various relevant ministries. Various technological innovation policy programs was created and implemented but they did not provide significant results. Through literature review from survey results and previous studies on the condition of the national innovation system (NIS) in Indonesia, as well as documents related to the actual role of Kemenristekdikti and other actors in the NIS, this study analyzes the condition of NIS in Indonesia. Based on the analysis, policies needed to strengthen Indonesia’s NIS is formulated. This needs an active role by Kemenristekdikti. The study shows that the key problem on the lack of technology innovation system in Indonesia is caused by the weak capacity of the actors of technological innovation (R&D institutions, university and the business sector / industry). Kemenristekdikti which is the main actor in NIS has a strategic role. This role is related to the coordination and joint management of each function in NIS. In order to improve the technological innovation system in Indonesia, the right prioritization of strategy development direction to increase the capacity of technological innovation of the actors in the innovation system is needed. Keywords: National Innovation System, technological innovation, capacity strengthening